Comparative Transcriptomics Analysis of the Responses of the Filamentous Fungus Glarea lozoyensis to Different Carbon Sources - Zhang, Ke; Huang, Baoqi; Yuan, Kai; Ji, Xiaojun; Song, Ping; Ding, Qingqing; Wang, Yuwen (Frontiers in Microbiology, 2020)
The natural product pneumocandin B0 is the precursor of the antifungal drug caspofungin. We found that replacing glucose in the initial fermentation medium with 20 g/L fructose is more conducive to pneumocandin B0 production and biomass accumulation. In order to explore the mechanism of the different metabolic responses to fructose and glucose, we used each as the sole carbon source, and the results showed that fructose increased the total pneumocandin B0 yield and biomass by 54.76 and 13.71%, respectively. Additionally, the fermentation time was shortened by 33.33% compared with glucose as a carbon source. Furthermore, we analyzed the differences of gene expression and metabolic pathways between the two different carbon sources by transcriptomic analysis. When fructose was used as the carbon source, genes related to the pentose phosphate pathway, glycolysis and branched-chain amino acid metabolism were significantly upregulated, resulting in increased intracellular pools of NADPH and acetyl-CoA in Glarea lozoyensis for cell growth and pneumocandin B0 product synthesis. Interestingly, the pneumocandin B0 biosynthetic gene cluster and the genes of the TCA were significantly downregulated, while the FAS genes were significantly upregulated, indicating that more acetyl-CoA was used for fatty acid synthesis. In particular, we found that excessive synthesis of fatty acids caused lipid accumulation, and lipid droplets can sequester lipophilic secondary metabolites such as pneumocandin B0 to reduce cell damage, which may also be an important reason for the observed increase of pneumocandin B0 yield. These results provide new insights into the relationship between pneumocandin B0 biosynthesis and carbon sources in G. lozoyensis. At the same time, this study provides important genomic information for improving pneumocandin B0 production through metabolic engineering strategies in the future.